Fiber reinforced geopolymer mortar grouting reinforcement method based on 3D printing structural surface

By using 3D printing technology to prepare the structural surface of the rock mass, and using basalt fiber reinforced geopolymer mortar for grouting and reinforcement, the shortcomings of cement-based materials and the brittleness of geopolymer materials in the existing technology are solved, and efficient and accurate reinforcement of the rock mass structure surface is achieved.

CN119877514APending Publication Date: 2025-04-25ZHENGZHOU UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510120316.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-25
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

In the grouting and reinforcement of rock mass structure surfaces, there are problems such as insufficient strength, poor stability, high carbon emissions and high energy consumption in the early stage of cement-based materials. The geopolymer materials themselves are brittle and have poor toughness, and the structural surfaces obtained by artificial prefabricated splitting are not exactly the same, resulting in poor test errors and reinforcement effects.

Method used

The structural surface reflecting the morphological characteristics of the real cracks was prepared based on 3D printing technology, and the basalt fiber reinforced geopolymer mortar was used for grouting and reinforcement. The structural surface damage characteristics were analyzed through shear tests to optimize the reinforcement effect.

Benefits of technology

It effectively improves the brittleness and toughness of the earth polymer material, improves the accuracy and effect of structural surface reinforcement, reduces engineering costs, and provides scientific reinforcement solutions and effect evaluation standards for actual projects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119877514A_ABST
    Figure CN119877514A_ABST
Patent Text Reader

Abstract

The invention relates to a fiber reinforced geopolymer mortar grouting reinforcement method based on a 3D printing structural surface. The method comprises the following steps: preparing basalt fiber reinforced geopolymer mortar; preparing a structural surface based on 3D printing; and the basalt fiber reinforced geopolymer mortar is grouted into the structural surface, and after the basalt fiber reinforced geopolymer mortar is solidified, the basalt fiber reinforced geopolymer mortar is maintained, so that the geopolymer mortar grouting reinforced structural surface is obtained. The invention further provides the fiber reinforced geopolymer mortar grouting reinforced structural surface of the 3D printing structural surface. By preparing the basalt fiber reinforced geopolymer mortar, the problems of high brittleness and poor toughness of the existing geopolymer are solved; the prepared basalt fiber reinforced geopolymer mortar is grouted into a structural plane prepared through 3D printing, grouting reinforcement is conducted on the structural plane, shear characteristic research is conducted on the structural plane obtained after reinforcement, and certain guidance is provided for actual engineering.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of rock and soil reinforcement, and in particular relates to a fiber reinforced geopolymer mortar grouting reinforcement method based on a 3D printed structural surface. Background Art

[0002] In recent years, my country's underground engineering has gradually developed into deep areas. During the excavation of deep engineering, many rock masses are broken, and there are a large number of joints and cracks inside the rock mass, which seriously affects the continuity and integrity of the rock mass, resulting in a decrease in the strength and overall stability of the rock mass. The mechanical properties of the structural surface determine the mechanical properties of the entire fractured rock mass. In engineering, fractured rock mass is deformed and damaged by external factors, generally by shear failure along the structural surface and expansion and penetration of the cracks. Therefore, it is particularly important to reinforce the structural surface to make the overall rock mass more stable.

[0003] At present, the use of grouting materials to reinforce the rock structure surface is a common and effective method to enhance the strength and overall stability of the rock mass, and has been widely used in various fields of geotechnical engineering. However, in current research, cement-based materials are mostly used for grouting reinforcement of structural surfaces. Cement-based materials are low-cost, resistant to high pressure, and durable, and are one of the most widely used building materials. For example, the patent number is 202111491044.5, and the patent name is wood nanocellulose-nanocement modified grouting material for deep earth engineering surrounding rock reinforcement and its preparation method. Among them, the use of wood nanocellulose reinforced cement-based composite materials greatly improves the mechanical properties of cement-based materials and solves the problem of poor injectability of cement-based materials in small pore formations, but the cement slurry has insufficient early strength and poor stability, and the initial and final setting times are long. In addition, the high carbon emissions and high energy consumption of cement slurry cause great pollution to the environment. Compared with traditional cement-based materials, geopolymer materials are simple to make, green and environmentally friendly, and have better mechanical properties than cement, and have been widely used in grouting reinforcement materials. For example, the patent number is CN202210049686.8, and the patent name is a fly ash geopolymer grouting material suitable for reinforcing weak surrounding rocks. The geopolymer grouting material is prepared by mixing fly ash with other auxiliary cementitious materials. Although it solves the problems of insufficient early strength and poor stability of traditional cement-based grouting materials, the geopolymer material itself has the problem of large brittleness and poor toughness. In order to improve the performance of geopolymer materials, it is necessary to study the shear characteristics of the structural surface of the grouting filling. However, the original rock structural surface obtained by artificial prefabricated splitting is not exactly the same, and certain errors will occur during the test. The structural surface cannot reflect the real fracture morphology characteristics, which in turn affects the structural surface grouting reinforcement effect in actual engineering. Summary of the invention

[0004] In view of the deficiencies of the above-mentioned prior art, the object of the present invention is to provide a fiber-reinforced geopolymer mortar grouting reinforcement method based on 3D printed structural surfaces. The method is based on 3D printing to prepare a structural surface that reflects the actual crack morphology characteristics, and to prepare basalt fiber-reinforced geopolymer mortar. The structural surface is grouting reinforced by basalt fiber-reinforced geopolymer mortar. After reinforcement, a shear test is performed and the structural surface failure characteristics are analyzed, so as to provide guidance for the grouting reinforcement of structural surfaces in actual engineering.

[0005] In order to solve the above technical problems, the present invention adopts the following technical solutions: The first implementation scheme provided by the present invention is to provide a fiber reinforced geopolymer mortar grouting reinforcement method based on a 3D printed structural surface, comprising the following steps: Prepare basalt fiber reinforced geopolymer mortar; Structural surface preparation based on 3D printing; The basalt fiber reinforced geopolymer mortar is grouting into the structural surface. After the basalt fiber reinforced geopolymer mortar is solidified, it is placed in a curing box for curing. To ensure the grouting effect, the basalt fiber reinforced geopolymer mortar grouting should be completed within half an hour after the slurry is prepared to obtain the geopolymer mortar grouting reinforcement structural surface.

[0006] Preferably, the basalt fiber reinforced geopolymer mortar is prepared from the following raw materials: Matrix material, alkali activator, water and basalt fiber, wherein the matrix material is fly ash, slag and quartz sand, and the water-binder ratio of the matrix material to water is 0.48-0.52; the alkali activator is water glass and sodium oxide, and the modulus of the alkali activator is 1.0-1.4; the mass content of the alkali activator is 4%-8%, and the mass content is the ratio of the mass of sodium oxide in the alkali activator to the total mass of fly ash and slag in the matrix material; The volume percentage of basalt fiber and geopolymer mortar is 0.2% to 0.6%, the length of basalt fiber is 3mm to 6mm, and the geopolymer mortar is prepared by mixing base material and alkali activator; If the length of basalt fiber is too short, the concrete void ratio will increase, the aggregation will be poor, the mixing will be uneven, and the strength will be reduced. If the length of basalt fiber is too long, the fiber arrangement will be uneven, the fiber will be tied, and other adverse effects will occur, which will reduce the strength of concrete. Therefore, in actual construction, the appropriate length of basalt fiber should be selected and controlled according to the location of the concrete and the use environment.

[0007] Preferably, the method for preparing the basalt fiber reinforced polymer mortar comprises the following steps: Orthogonal experiments were designed based on the mass dosage of alkali activator, water-cement ratio and water glass modulus as control factors, and the rheological and mechanical properties of the samples under different proportions were compared. Combined with the requirements for the injectability of geopolymer mortar slurry at the construction site, the geopolymer mortar proportion was obtained. The basalt fiber is subjected to alkali corrosion modification to obtain alkali-corroded basalt fiber. The specific alkali corrosion modification method is as follows: the basalt fiber is dried in an electric heating blower at 250° C. for 1 hour to remove the organic impregnant on the surface thereof, and after drying, the basalt fiber is placed in a 1 mol / L sodium hydroxide solution, first stirred with a glass rod for 5 minutes and then soaked for 25 minutes, and then taken out and washed with distilled water to neutrality, and then dried in an electric heating blower at 250° C. for 1 hour to obtain the alkali-corroded basalt fiber; Alkali-corroded basalt fiber was added to the geopolymer mortar made according to this ratio to prepare basalt fiber reinforced geopolymer mortar. The rheological and mechanical properties of various basalt fiber reinforced geopolymer mortars were compared. Combined with the requirements of the construction site for the injectability of the basalt fiber reinforced geopolymer mortar slurry, the optimal ratio of basalt fiber reinforced geopolymer mortar was selected.

[0008] Preferably, the method for preparing a structural surface based on 3D printing comprises the following steps: Original rock acquisition; The original rock is split and the structural surface with central position and complete shape is selected; The structural surface of the original rock is modeled by three-dimensional scanning technology and the structural surface roughness coefficient is calculated. The structural surface roughness coefficient is calculated by the method given in the prior art. The structural surface panel is prepared by 3D printing according to the obtained structural surface roughness coefficient; The structural surface panel is placed in a customized mold for sample casting. After casting, the sample is demoulded to obtain the lower plate of the sample. The lower plate is then placed in the mold, and the upper plate of the sample is cast according to the lower plate of the sample. At the same time, the casting height is controlled according to the crack opening for demoulding and curing to obtain a structural surface based on 3D printing.

[0009] Preferably, the sample casting material consists of cement, quartz sand and water, wherein the mass ratio of cement, quartz sand and water is 1:1:0.4.

[0010] Preferably, the parent rock is granite or marble, the structural surface roughness coefficient of granite is 6, and the structural surface roughness coefficient of marble is 9.

[0011] Preferably, the structural surface of the original rock is obtained by cutting and splitting the original rock with an original rock splitting device. During splitting, a clamp with tooth-like protrusions is used, and the position of the tooth-like protrusions corresponds to the position of the wire cutting crack, which facilitates the splitting of the original rock under the action of normal force.

[0012] The second implementation scheme provided by the present invention is to provide a geopolymer mortar grouting reinforcement structural surface prepared by a fiber reinforced geopolymer mortar grouting reinforcement method based on a 3D printing structural surface.

[0013] Compared with the prior art, the present invention has the following beneficial effects: 0. The present invention prepares basalt fiber reinforced geopolymer mortar by adding basalt fiber to geopolymer mortar, which can effectively improve the existing geopolymer itself, which has large brittleness and poor toughness; then the prepared basalt fiber reinforced geopolymer mortar is grouting into the structural surface prepared by 3D printing technology, and the structural surface is grouting reinforced, and the shear property study of the obtained structural surface after reinforcement can solve the problem that the original rock structural surface obtained by artificial prefabricated splitting is not completely the same, which causes certain errors in the test during the test and cannot reflect the structural surface of the real crack morphology. By studying the shear properties of the structural surface given by the present invention, the grouting reinforcement effect of the structural surface can be obtained, thereby providing certain guidance for the grouting reinforcement in actual engineering and the effect evaluation of basalt fiber reinforced geopolymer mortar.

[0014] 2. The present invention uses 3D printing technology to reconstruct the original rock structure surface, which not only restores the morphological characteristics of the structure surface to the greatest extent, but also can reuse the structure surface panel casting samples in the grouting reinforcement test, saving manpower and material resources and reducing economic costs. This method is also applicable to grouting tests of various grouting materials.

[0015] 3. The present invention also provides reinforcement effect evaluation and structural surface damage characteristic analysis steps to obtain the optimal basalt fiber reinforced geopolymer mortar test ratio and parameter standards for structural surface grouting reinforcement influencing factors; and analyzes the connection mode of the interface transition zone with the help of electron microscope scanning technology. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 It is a flow chart of the grouting method of the present invention.

[0017] Figure 2 This is a microstructure diagram of a basalt fiber reinforced geopolymer mortar sample magnified 1000 times in an embodiment of the present invention.

[0018] Figure 3 This is a polylactic acid structural surface panel made by 3D printing technology in the embodiment of the present invention.

[0019] Figure 4 This is a microstructure diagram of a structural surface debris sample that fell off during the shear test in an embodiment of the present invention, magnified 500 times. DETAILED DESCRIPTION

[0020] The specific embodiments of the present invention are described in detail below, but it should be understood that the protection scope of the present invention is not limited by the specific embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work belong to the protection scope of the present invention. The experimental methods described in the embodiments of the present invention are conventional methods unless otherwise specified.

[0021] The inventors found that in current practical projects, there is still a lack of a system solution that can organically combine basalt fiber reinforced geopolymer mortar with a structural surface that reflects the real crack morphology to optimize the entire process of basalt fiber reinforced geopolymer mortar grouting reinforcement. In view of this, we proposed a basalt fiber reinforced geopolymer mortar grouting reinforcement method based on 3D printed structural surface to solve the above problems.

[0022] Example 1 like Figure 1 As shown, a fiber reinforced geopolymer mortar grouting reinforcement method based on a 3D printed structural surface comprises the following steps: (1) Preparing basalt fiber reinforced geopolymer mortar includes the following steps: Select the matrix material. In this embodiment, the matrix materials selected are fly ash, slag and quartz sand, and the water-binder ratio is 0.50; Preparation of alkaline activator: In this embodiment, the alkaline activator selected is water glass and sodium oxide, and the modulus of the alkaline activator is 1.2; An orthogonal experiment was designed based on the mass dosage of alkali activator, water-cement ratio and water glass modulus as control factors. The fluidity, initial setting time and final setting time of the samples under different material ratios under different control factors of the orthogonal experimental design were compared, and compression and shear tests were carried out. Combined with the requirements of the construction site for the injectability of the slurry, the optimal ratio of geopolymer mortar and basalt fiber alkali erosion improvement were selected; the optimal ratio of geopolymer mortar selected was a water-cement ratio of 0.50, an alkali activator modulus of 1.2, and an alkali dosage of 8%. The orthogonal experimental design was divided into 9 groups.

[0023] Then, alkali-corroded basalt fibers with different parameter standards were added to the best mix ratio samples of geopolymer mortar, and the rheological and mechanical properties of the samples under each mix ratio were compared. Combined with the requirements of the construction site for the injectability of the slurry, the best mix ratio of basalt fibers was selected. The best mix ratio of basalt fibers selected was 4.5 mm in fiber length and 0.4% by volume of basalt fibers to geopolymer mortar. The preparation of geopolymer mortar and the optimization process of alkali attack of basalt fiber are both existing technologies and will not be described in detail here; (2) Preparation of structural surface samples based on 3D printing, including the following steps: Original rock acquisition; The original rock is split and the structural surface with central position and complete shape is selected; The structural surface is modeled using 3D scanning technology and the structural surface roughness coefficient is calculated. The structural surface roughness coefficient of granite is 6. The structural surface panel is prepared by using 3D printing technology according to the obtained structural surface roughness coefficient; Put the structural surface panel into the customized mold, cast the sample, and get the lower plate of the sample after demoulding. Then put the lower plate into the mold, cast the upper plate of the sample according to the lower plate of the sample, and control the casting height according to the crack opening. Demould and maintain. The sample casting materials are composed of cement, quartz sand and water, and the mass ratio of cement, quartz sand and water is 1:1:0.4; The original rocks used are granite and marble. When splitting the original rock, the original rock splitting device is used, and a tooth-like protrusion is provided in the middle of the base and the cover plate, so that the mold can split the original rock under the action of the normal force. Three-dimensional scanning and 3D printing technologies are existing technologies. For example, the invention is called "Method for Making Joint Samples with Specific Geometric Feature Structural Surfaces by Using 3D Printing", and the public document with application number 201510257888.1 has a detailed description of the sample preparation process. The polylactic acid structural surface panel made by 3D printing technology, such as Figure 3 As shown, polylactic acid structural surface panels and customized cast iron molds are used to cast the upper and lower plates of the specimens, and the pouring height is controlled to reserve space for the cracks, thereby obtaining a batch of standard specimens with the same structural surface shape.

[0024] (3) Preparation of samples for basalt fiber reinforced geopolymer mortar grouting reinforcement of structural surfaces When basalt fiber reinforced geopolymer mortar is grouting into structural surface samples with different structural surface roughness coefficients and crack openings, in order to ensure the grouting effect, the grouting should be completed within half an hour after the slurry is prepared.

[0025] The structural surface roughness coefficient is an important parameter affecting the shear strength of the structural surface, and the shear strength is an important factor affecting the stability of the rock mass. When the crack opening exceeds a certain value, the stability of the rock will be significantly reduced, which may lead to the destruction of the rock mass.

[0026] After the slurry solidifies, the specimens are placed in a curing box for 7 days; (4) The shear characteristics of the obtained structural surface are studied, which includes the evaluation of the reinforcement effect and the analysis of the structural surface failure characteristics, specifically: The study of the shear characteristics of the structural surface includes the evaluation of the reinforcement effect of the structural surface and the analysis of the failure characteristics of the structural surface, which is specifically composed of the following steps: A shear test was conducted on the structural surface treated with the grouting reinforcement method, and the obtained data was analyzed by direct shear test; The shear strength of the grouting reinforced structural surface is studied by taking different roughness, normal stress and the centerline cutting depth of the original rock structural surface obtained through the structural surface shear test as the control factors. The structural surface debris that fell off during the shear test was scanned by an electron microscope to analyze the connection mode of the interface transition zone.

[0027] Example 2 like Figure 1 As shown, a fiber reinforced geopolymer mortar grouting reinforcement method based on a 3D printed structural surface comprises the following steps: (1) Preparing basalt fiber reinforced geopolymer mortar includes the following steps: Select the matrix material. In this embodiment, the matrix materials selected are fly ash, slag and quartz sand, and the water-binder ratio is 0.48; Preparation of alkaline activator. In this embodiment, the alkaline activator is water glass and sodium oxide, and the modulus of the alkaline activator is 1.2; An orthogonal experiment was designed based on the mass dosage of alkali activator, water-cement ratio and water glass modulus as control factors. The fluidity, initial setting time and final setting time of the samples under different material ratios under different control factors of the orthogonal experiment design were compared, and compression shear and tensile tests were carried out. Combined with the requirements of the construction site for the injectability of the slurry, the optimal ratio of geopolymer mortar and basalt fiber alkali erosion improvement were selected; the orthogonal experiment control factors were: water-cement ratio of 0.50, alkali activator modulus of 1.2, alkali dosage of 8%, and the orthogonal experiment design was divided into 9 groups.

[0028] Alkali-corroded basalt fibers with different parameter standards were added to the best mix ratio samples of geopolymer mortar, and the rheological and mechanical properties of the samples under each mix ratio were compared. Combined with the requirements of the construction site for the injectability of the slurry, the best mix ratio of basalt fibers was selected; the excellent mix ratio of basalt fibers selected was 4.5 mm in fiber length and 0.4% by volume of basalt fibers to geopolymer mortar; The preparation of geopolymer mortar and the optimization process of alkali attack of basalt fiber are both existing technologies and will not be described in detail here; (2) Preparation of structural surface samples based on 3D printing, including the following steps: Original rock acquisition; The original rock is split and the structural surface with central position and complete shape is selected; The structural surface is modeled using 3D scanning technology and the structural surface roughness coefficient is calculated. The structural surface roughness coefficient of marble is 9. The structural surface panel is prepared by using 3D printing technology according to the obtained structural surface roughness coefficient; Put the structural surface panel into the customized mold, cast the sample, and get the lower plate of the sample after demoulding. Then put the lower plate into the mold, cast the upper plate of the sample according to the lower plate of the sample, and control the casting height according to the crack opening. Demould and maintain. The sample casting materials are composed of cement, quartz sand and water, and the mass ratio of cement, quartz sand and water is 1:1:0.4; The original rocks used are granite and marble. When splitting the original rock, the original rock splitting device is used, and a tooth-like protrusion is provided in the middle of the base and the cover plate, so that the mold can split the original rock under the action of the normal force. Three-dimensional scanning and 3D printing technologies are existing technologies. For example, the invention is called "Method for Making Joint Samples with Specific Geometric Feature Structural Surfaces by Using 3D Printing", and the public document with application number 201510257888.1 has a detailed description of the sample preparation process. The polylactic acid structural surface panel made by 3D printing technology, such as Figure 3 As shown, polylactic acid structural surface panels and customized cast iron molds are used to cast the upper and lower plates of the specimens, and the pouring height is controlled to reserve space for the cracks, thereby obtaining a batch of standard specimens with the same structural surface shape.

[0029] (3) Preparation of samples for basalt fiber reinforced geopolymer mortar grouting reinforcement of structural surfaces When basalt fiber reinforced geopolymer mortar is grouting into structural surface samples with different structural surface roughness coefficients and crack openings, in order to ensure the grouting effect, the grouting should be completed within half an hour after the slurry is prepared.

[0030] After the slurry solidifies, the specimens are placed in a curing box for 7 days; (4) The shear characteristics of the obtained structural surface are studied, which includes the evaluation of the reinforcement effect and the analysis of the structural surface failure characteristics, specifically: The study of the shear characteristics of the structural surface includes the evaluation of the reinforcement effect of the structural surface and the analysis of the failure characteristics of the structural surface, which is specifically composed of the following steps: A shear test was conducted on the structural surface treated with the grouting reinforcement method, and the obtained data was analyzed by direct shear test; The shear strength of the grouting reinforced structural surface is studied by taking different roughness, normal stress and the centerline cutting depth of the original rock structural surface obtained through the structural surface shear test as the control factors. The structural surface debris that fell off during the shear test was scanned by an electron microscope to analyze the connection mode of the interface transition zone.

[0031] Example 3 like Figure 1 As shown, a fiber reinforced geopolymer mortar grouting reinforcement method based on a 3D printed structural surface comprises the following steps: (1) Preparing basalt fiber reinforced geopolymer mortar includes the following steps: Select the matrix material. In this embodiment, the matrix materials selected are fly ash, slag and quartz sand, and the water-binder ratio is 0.52; Preparation of alkaline activator: In this embodiment, the alkaline activator is prepared from water glass and sodium oxide, and the modulus of the alkaline activator is 1.4; Orthogonal experiment was designed with the mass dosage of alkali activator, water-cement ratio and water glass modulus as control factors. The fluidity, initial setting time and final setting time of the samples under the material ratios with different control factors were compared through orthogonal experimental design, and compression shear and tensile tests were carried out. Combined with the requirements of the construction site for the injectability of the slurry, the best ratio of geopolymer mortar and basalt fiber alkali corrosion improvement were selected. The orthogonal experimental control factors were: water-cement ratio of 0.52, alkali activator modulus of 1.4, alkali dosage of 4%, and the orthogonal experimental design was divided into 9 groups.

[0032] Alkali-corroded basalt fibers with different parameter standards were added to the best mix ratio samples of geopolymer mortar, and the rheological and mechanical properties of the samples under each mix ratio were compared. Combined with the requirements of the construction site for the injectability of the slurry, the best mix ratio of basalt fibers was selected; the excellent mix ratio of basalt fibers selected was 4.5 mm in fiber length and 0.4% by volume of basalt fibers to geopolymer mortar; The preparation of geopolymer mortar and the optimization process of alkali attack of basalt fiber are both existing technologies and will not be described in detail here; (2) Preparation of structural surface samples based on 3D printing, including the following steps: Original rock acquisition; The original rock is split and the structural surface with central position and complete shape is selected; The structural surface is modeled using 3D scanning technology and the structural surface roughness coefficient is calculated. The structural surface roughness coefficient of granite is 6. The structural surface panel is prepared by using 3D printing technology according to the obtained structural surface roughness coefficient; Put the structural surface panel into the customized mold, cast the sample, and get the lower plate of the sample after demoulding. Then put the lower plate into the mold, cast the upper plate of the sample according to the lower plate of the sample, and control the casting height according to the crack opening. Demould and maintain. The sample casting materials are composed of cement, quartz sand and water, and the mass ratio of cement, quartz sand and water is 1:1:0.4; The original rocks used are granite and marble. When splitting the original rock, the original rock splitting device is used, and a tooth-like protrusion is provided in the middle of the base and the cover plate, so that the mold can split the original rock under the action of the normal force. Three-dimensional scanning and 3D printing technologies are existing technologies. For example, the invention is called "Method for Making Joint Samples with Specific Geometric Feature Structural Surfaces by Using 3D Printing", and the public document with application number 201510257888.1 has a detailed description of the sample preparation process. The polylactic acid structural surface panel made by 3D printing technology, such as Figure 3As shown, polylactic acid structural surface panels and customized cast iron molds are used to cast the upper and lower plates of the specimens, and the pouring height is controlled to reserve space for the cracks, thereby obtaining a batch of standard specimens with the same structural surface shape.

[0033] (3) Preparation of samples for basalt fiber reinforced geopolymer mortar grouting reinforcement of structural surfaces When basalt fiber reinforced geopolymer mortar is grouting into structural surface samples with different structural surface roughness coefficients and crack openings, in order to ensure the grouting effect, the grouting should be completed within half an hour after the slurry is prepared.

[0034] After the slurry solidifies, the specimens are placed in a curing box for 7 days; (4) The shear characteristics of the obtained structural surface are studied, which includes the evaluation of the reinforcement effect and the analysis of the structural surface failure characteristics, specifically: The study of the shear characteristics of the structural surface includes the evaluation of the reinforcement effect of the structural surface and the analysis of the failure characteristics of the structural surface, which is specifically composed of the following steps: A shear test was conducted on the structural surface treated with the grouting reinforcement method, and the obtained data was analyzed by direct shear test; The shear strength of the grouting reinforced structural surface is studied by taking different roughness, normal stress and the centerline cutting depth of the original rock structural surface obtained through the structural surface shear test as the control factors. The structural surface debris that fell off during the shear test was scanned by an electron microscope to analyze the connection mode of the interface transition zone.

[0035] The above-mentioned Examples 1 to 3 are all capable of reinforcing the structural surface. The following Example 1 is a fiber-reinforced geopolymer mortar grouting reinforcement method based on 3D printed structural surface, as well as the optimal solution for the prepared structural surface and application.

[0036] Experimental verification (1) Scanning electron microscope image of basalt fiber reinforced geopolymer mortar The basalt fiber reinforced geopolymer mortar was scanned using a Quanta250 electron microscope to analyze its microstructural characteristics. The scanning results are shown in the figure below. Figure 2 As shown, from Figure 2 It can be seen that after basalt fiber is added to geopolymer mortar, after mortar stirring and solidification, basalt fiber is embedded in geopolymer gel and surrounded by geopolymer mortar gel. Basalt fiber has good bonding force in geopolymer mortar, which improves the density of geopolymer mortar structure. Therefore, during the test, the mechanical properties of geopolymer mortar samples with basalt fiber added are more excellent.

[0037] (2) Shear test of structural surface specimens For the reinforced structural surface samples, 8 groups of tests were set up according to the size of the crack opening, the size of the structural surface roughness coefficient and the size of the normal stress, as shown in Table 1; for the unreinforced structural surface samples, 4 groups of tests were set up according to the size of the structural surface roughness coefficient and the size of the normal stress, as shown in Table 2; the grouting effect was evaluated by comparing the degree of improvement in the shear strength of the structural surface before and after grouting, and all structural acoustic emission technology was used to monitor the failure process of each group of samples and the subsequent analysis of the influence of various control factors. After the shear test is completed, the failure morphology of the sample should be guaranteed as much as possible during the process of removing the damaged sample, in preparation for the subsequent evaluation of the reinforcement effect and analysis of the control factors.

[0038] The roughness coefficient, normal stress and crack opening in Table 1 are three test influencing factors. We made test blocks for testing based on these three factors.

[0039] By analyzing the structural surface failure characteristics of each group of samples and the various parameters of the acoustic emission technology during the entire shearing process, the reinforcement effect of basalt fiber reinforced geopolymer mortar was preliminarily evaluated. In this embodiment, the basalt fiber reinforced geopolymer mortar grouting reinforcement effect is significant, and the mechanical properties are significantly improved compared with the unreinforced group of samples.

[0040] During the test, we first obtained the tangential displacement-shear stress curve of each group in the shear test. From the curve, we can know the data such as peak shear stress and residual shear stress. Then, taking the normal force as an example, we analyzed the influence of the normal force on the shear performance of the structural surface.

[0041] The first step is to analyze the trend of the curve and compare the tangential displacement-shear stress curves obtained by direct shear tests on structural surfaces under different normal stress conditions. It can be seen that the tangential displacement-shear stress curves in the direct shear test of the grouting filling structural surface under different normal stresses are basically consistent, with obvious peak shear stresses. After the curve reaches the peak shear stress, the shear stress will also drop significantly. Finally, with the continuous increase of the tangential displacement, the shear stress stabilizes to a residual value, and the overall curve is a nonlinear curve. When the roughness of the structural surface is consistent with the crack opening of the structural surface, the peak shear stress and residual shear stress of the grouting filling structural surface increase with the increase of normal stress.

[0042] The second step is to analyze the percentage of improvement. For example, when the crack opening of the grouting reinforced structure is 4mm, the structural surface roughness coefficient is 6, and the normal stress is 2MPa, the peak shear stress of the grouting reinforced sample is increased by 81% and the residual shear stress is increased by 38.8% compared with the non-grouting reinforced sample with a roughness coefficient of 6 and a normal stress of 2MPa.

[0043] When the crack opening of the structural surface reinforced by grouting is 4mm, the structural surface roughness is 6, and the normal stress is 4MPa, the peak shear stress increases by 57.1% and the residual tangential load increases by 90.9% compared with the crack opening of the structural surface reinforced by grouting is 4mm, the structural surface roughness is 6, and the normal stress is 2MPa.

[0044] The crack opening of the structural surface reinforced by grouting is 4mm, the structural surface roughness is 6, and the peak shear load at normal stress of 4MPa is 75% higher than that of the structural surface of the non-grouting group, and the residual shear load is increased by 46.6%.

[0045] The crack opening of the structural surface reinforced by grouting is 4mm, the structural surface roughness is 6, and the peak shear load at normal stress of 2MPa is 27.9% higher than that of the non-grouting group, and the residual shear load is increased by 27.2%.

[0046] By analyzing the data in Table 1 and Table 2, we can find that: (1) The greater the normal force, the greater the peak shear strength of the grouting filling structure surface; (2) When the normal stress and crack opening are constant, the greater the roughness, the greater the shear strength and residual strength of the grouting filling structure surface; (3) As the crack opening increases, the peak shear strength of the filling grouting structure surface decreases.

[0047] It must be pointed out that these laws and analyses are only the analysis and summary of the experiment. If they are generalized, there will be many shortcomings. For example, in (1), the effect of the normal force is limited and shows a positive correlation within the experimental range. When the normal force is large, specific analysis is required, and the effect may remain unchanged or decrease.

[0048] Table 1: Shear test of grouting reinforced structural surface Table 2: Shear test of structural surface without grouting reinforcement (3) Electron micrograph of the structural surface debris sample that fell off during the shear test The mechanical properties of grouting-reinforced rock mass are closely related to the mechanical properties of the slurry consolidation body and the slurry-rock interface. The pores and micro-cracks near the slurry-rock interface are also closely related to the shear properties of the grouting-reinforced rock mass. In order to characterize the micro-structural characteristics of the slurry-rock interface, the Quanta250 electron microscope scanning equipment was used to scan the slurry-rock interface debris that fell off during the shear test and analyze the micro-structural characteristics of the interface. The scanning results are shown in Figure 2. Figure 4 In this embodiment, from Figure 4It can be clearly seen that there are a large number of pores in the transition zone of the slurry-rock interface, which indicates that the porosity near this area is greater than that of the rock sample and the slurry consolidation body far away from this area. In addition, since a complex three-dimensional structural surface is used in the test, the structural surface is uneven, and its contact area with the slurry is larger than that of the ordinary regular serrated structural surface. Therefore, more cementitious material particles are accumulated in the interface transition zone, and the bonding structure formed is better, which can achieve the grouting reinforcement effect of the structural surface.

[0049] The present invention improves the existing geopolymer's inherent brittleness and poor toughness by preparing basalt fiber reinforced geopolymer mortar; then the prepared basalt fiber reinforced geopolymer mortar is grout-injected into the structural surface prepared by 3D printing technology, and the structural surface is reinforced by grouting. After reinforcement, the shear characteristics of the obtained structural surface are studied. This operational structural surface grouting reinforcement method provides certain guidance for grouting reinforcement in actual engineering and the effect evaluation of basalt fiber reinforced geopolymer mortar.

[0050] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.

Claims

1. A fiber-reinforced geopolymer mortar grouting reinforcement method based on a 3D printed structural surface, characterized in that: The steps include: Prepare basalt fiber reinforced geopolymer mortar; Structural surface preparation based on 3D printing; The basalt fiber reinforced geopolymer mortar is grouting into the structural surface, and the basalt fiber reinforced geopolymer mortar is cured after solidification to obtain the geopolymer mortar grouting reinforced structural surface.

2. The fiber-reinforced geopolymer mortar grouting reinforcement method based on 3D printed structural surface according to claim 1, characterized in that: The basalt fiber reinforced geopolymer mortar is prepared from the following raw materials: Matrix material, alkali activator, water and basalt fiber, wherein the matrix material is fly ash, slag and quartz sand, and the water-binder ratio of the matrix material to water is 0.48-0.52; the alkali activator is water glass and sodium oxide, and the modulus of the alkali activator is 1.0-1.4; the mass content of the alkali activator is 4%-8%, and the mass content is the ratio of the mass of sodium oxide in the alkali activator to the total mass of fly ash and slag in the matrix material; The volume percentage of basalt fiber and geopolymer mortar is 0.2% to 0.6%, the length of basalt fiber is 3mm to 6mm, and the geopolymer mortar is prepared by mixing base material and alkali activator.

3. The fiber-reinforced geopolymer mortar grouting reinforcement method based on 3D printed structural surface according to claim 2, characterized in that: The preparation method of the basalt fiber reinforced geopolymer mortar comprises the following steps: Obtaining geopolymer mortar mix ratio; Alkali-corroded basalt fibers are added to the geopolymer mortar prepared according to the ratio to prepare basalt fiber reinforced geopolymer mortar, wherein the alkali-corroded basalt fibers are prepared by modifying basalt fibers by alkali corrosion.

4. The fiber-reinforced geopolymer mortar grouting reinforcement method based on 3D printed structural surface according to claim 1, characterized in that: The method for preparing a structural surface based on 3D printing comprises the following steps: Use 3D scanning technology to model the structural surface of the original rock and calculate the structural surface roughness coefficient; The structural surface panel is prepared by 3D printing according to the obtained structural surface roughness coefficient; The structural surface panel is placed in a customized mold for sample casting. After casting, it is demolded and cured to obtain a structural surface based on 3D printing.

5. The fiber-reinforced geopolymer mortar grouting reinforcement method based on 3D printed structural surface according to claim 4, characterized in that: The sample casting materials consist of cement, quartz sand and water, wherein the mass ratio of cement, quartz sand and water is 1:1:0.

4.

6. The fiber-reinforced geopolymer mortar grouting reinforcement method based on 3D printed structural surface according to claim 4, characterized in that: The original rock is granite or marble, wherein the structural surface roughness coefficient of granite is 6, and the structural surface roughness coefficient of marble is 9.

7. The fiber-reinforced geopolymer mortar grouting reinforcement method based on 3D printed structural surface according to claim 4, characterized in that: The structural surface of the original rock is obtained by cutting and splitting the original rock through an original rock splitting device.

8. A geopolymer mortar grouting reinforcement structural surface prepared by the grouting reinforcement method of fiber reinforced geopolymer mortar based on 3D printed structural surface as described in any one of claims 1 to 7.

Citation Information

Patent Citations

  • Joint test specimen method using 3D (three-dimensional) printing for making structure surface containing specific geometrical characteristics

    CN104807685A

  • Wood nano-cellulose-nano-cement modified grouting material for deep ground engineering surrounding rock reinforcement and preparation method thereof

    CN114085059A

  • Full-section deep hole grouting reinforcement method

    CN114483048A